HMPA-Free Generation of Trialkylsilyllithium Reagents and Its Applications to the Synthesis of Silylboronic Esters - Kamio, Shintaro; Imagawa, Taiki; Nakamoto, Masaaki; Oestreich, Martin; Yoshida, Hiroto (Synthesis, 2021)
Trialkylsilyllithium species have turned out to be facilely generated by treating hexaalkyldisilanes with methyllithium in the presence of tris(N,N-tetramethylene)phosphoric triamide (TPPA) as an activator, which can be trapped by boron electrophiles to afford silylboronic esters including long-awaited Me3Si–B(pin).
Keywords: trialkylsilyllithium; hexaalkyldisilane; silylboronic ester; TPPA; HMPA